PENERAPAN KOLAM KARANTINA IKAN HIAS BERBASIS TEKNOLOGI RAMAH LINGKUNGAN DI POKDAKAN MAKMUR REJEKI KABUPATEN TULUNGAGUNG - Uun Yanuhar; Muhammad Musa; Herly Evanuarini; Dyah Kinasih Wuragil; Heru Suryanto; Muhammad Sumsanto; Nico Rahman Caesar (Universitas Mataram, 2023)
The goldfish (Carassius auratus) has become one of the most sought-after ornamental fish today. The continuously rising market demand for goldfish as pets and decorative objects has driven the growth of the goldfish (Carassius auratus) farming industry. However, fish farmers still face difficulties in controlling the health of the fish and the quality of their water. The aquatic environment plays a crucial role in the growth of goldfish (Carassius auratus). Therefore, environmental management and fish health are essential in goldfish (Carassius auratus) farming. After the PKM Team analyzed the existing issues, the activities carried out to address these issues include the implementation of an Environmentally Friendly Recirculating Aquaculture System (RAS) in the goldfish (Carassius auratus) farming ponds. In this PKM program, water filtration will consist of mechanical filters, biological filters, chemical filters, and UV light. The results of the community service activities conducted by the PKM Team with their partners include increased knowledge, improved skills, increased production capacity, and increased profitability. Keywords: